The Role And The Process Of Institutional Entrepreneurship In The Implementation Of Accrual Accounting By The Malaysian Federal Government - Mahadi, Rozaidy (2019)
Recognising that accounting change is a complex process involving different types of forces and agents, there is an urgency to explain how accrual accounting as a product of change is able to become a catalyser for institutional reform through the process of institutional entrepreneurship. Hence, this study integrates multiple strings of institutional theory, namely, logics, institutional entrepreneurship, and rhetoric to explain how the Accountant’s General Department (AGD) initiated accrual accounting change in Malaysia’s federal government and institutionalised it. The study adopted an interpretive case study as the research’s methodological paradigm. From the case findings, it can be seen that there are two exogenous forces that pushed the federal government to adopt accrual accounting in the Malaysian federal government, and both forces concomitantly worked at the same. The inducement of both exogenous forces in the field has redefined the institutional logics at both federal and departmental levels. Subsequently, isomorphism pressures pushed the federal government’s logic from bureaucracy to managerialism, and the transformation of the federal government logic subsequently influenced the assimilation of public sector accountants’ logic from scorekeeper to professionalism-bureaucracy logic. Hence, due to the AGD’s location in a highly embedded field, the adoption of professionalism-bureaucracy logic did not significantly enhance the AGD’s roles and functions in the government.